FUNGSI EKOWISATA SEBAGAI SARANA EDUKASI PELESTARIAN HUTAN TROPIS DI KABIL, BATAM - Robert Halim; Diah Anggraini (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Forests are one of the largest oxygen producers on Earth and are home to many types of plants and animals. The existence of forests on Earth is very important because their absence would have fatal consequences for all life. One of the impacts due to the reduced number of forests is global warming, flooding, reduced oxygen supply and landslides. The word deforestation is no longer a "taboo" in forest management in Indonesia. The area of natural forests in Indonesia continues to decrease every year. According to Global Forest Watch, Indonesia's forests decreased by 40% in 2018. Agriculture, illegal logging and mining are commercial activities as the main drivers of deforestation. One of them is that the city of Batam has experienced a 45% reduction in the amount of forested area each year due to various factors, one of which is illegal logging in the city of Batam. The biophilic approach was chosen in the design of issues regarding deforestation to provide a positive relationship between humans and nature to achieve environmental, moral, social and economic benefits. This project is expected through entertainment tourism activities to educate residents to better understand the problem of deforestation and increase awareness of environmental improvements, especially tropical forests in Indonesia. Keywords:  Batam; ecotourism; forest; prerservation; tropical forestAbstrakHutan adalah salah satu penghasil oksigen di Bumi dan tempat hidup berbagai jenis tanaman dan hewan. Keberadaan hutan di Bumi sangat penting karena ketidakhadirannya akan memiliki konsekuensi fatal bagi semua kehidupan. Salah satu dampak akibat berkurangnya jumlah hutan adalah pemanasan global, banjir, berkurangnya pasokan oksigen dan tanah longsor. Kata deforestasi sudah tidak lagi menjadi “tabu” dalam pengelolaan hutan di Indonesia.Luas hutan alam di Indonesia terus berkurang setiap tahunnya. Berdasarkan Global Forest Watch, terjadi penurunan hutan dii Indonesia sebesar 40% pada 2018. Agrikultur, penembangan liar dan pertambangan merupakan kegiatan komersial sebagai pendorong utama deforestasi. Salah satunya yaitu kota Batam telah mengalami pengurangan 45% jumlah daerah berhutan setiap tahunnya karena berbagai faktor, salah satunya adalah pembalakan liar di Kota Batam. Pendekatan biophilic dipilih dalam desain persoalan mengenai deforestasi untuk memberikan hubungan positif antar manusia dengan alam untuk mencapai manfaat lingkungan, moral, sosial dan ekonomi. Proyek ini diharapkan melalui kegiatan wisata hiburan dapat mengedukasi penduduk agar lebih memahami persoalan deforestasi dan meningkatkan kepedulian pada perbaikan lingkungan khususnya hutan tropis di indonesia.